2012
DOI: 10.1111/j.1502-3931.2011.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethological analysis of the trace fossil Zoophycos : hints from the Arctic Ocean

Abstract: Löwemark, L. 2011: Ethological analysis of the trace fossil Zoophycos: Hints from the Arctic Ocean. Lethaia, Vol. 45, pp. 290–298. The distribution of the trace fossil Zoophycos in Quaternary marine sediments from the Arctic Ocean was studied in twelve piston and gravity cores retrieved during the Swedish icebreaker expeditions YMER80, Arctic Ocean‐96 and LOMROG I & II. The sampled cores span an area from the Makarov Basin to the Fram Strait. Zoophycos was only found in two cores taken at more than 2 km water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…These outflowing Arctic bottom waters are among the coldest on Earth, and form through a set of complex mechanisms in the Arctic Ocean (Rudels et al, 2005;Rudels and Friedrich, 2000). Consequently, if conditions are bad for Zoophycos-producing animals in the central Arctic, as indicated by radiograph studies showing only rare occurrences (Löwemark, 2012), then the number of larvae reaching and colonizing the Fram Strait area can be expected to be very low, resulting in few or no Zoophycos burrows. This kind of control on the distribution of benthic populations has been proposed both for intertidal (Roughgarden et al, 1988) and deep-marine communities (Bouchet and Taviani, 1992).…”
Section: Cache Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…These outflowing Arctic bottom waters are among the coldest on Earth, and form through a set of complex mechanisms in the Arctic Ocean (Rudels et al, 2005;Rudels and Friedrich, 2000). Consequently, if conditions are bad for Zoophycos-producing animals in the central Arctic, as indicated by radiograph studies showing only rare occurrences (Löwemark, 2012), then the number of larvae reaching and colonizing the Fram Strait area can be expected to be very low, resulting in few or no Zoophycos burrows. This kind of control on the distribution of benthic populations has been proposed both for intertidal (Roughgarden et al, 1988) and deep-marine communities (Bouchet and Taviani, 1992).…”
Section: Cache Modelmentioning
confidence: 98%
“…Previous studies have indicated a strong preference for calm conditions, relatively low sedimentation rates, intermediate organic carbon content, and possibly a preference for settings with a strong seasonal shift in the food flux (Löwemark, 2012;Löwemark et al, 2006;Löwemark and Schäfer, 2003;Wetzel and Werner, 1981). Especially the Greenland and Norwegian Seas are characterized by extremes both in the composition of the sediment, which often contains high amounts of ice rafted debris, and in the extreme differences in primary productivity between winter and summer.…”
Section: Introductionmentioning
confidence: 97%
“…Modern deep‐sea Zoophycos have been also extensively studied using X‐ray radiographs (Wetzel & Werner ; Löwemark & Schäfer ; Löwemark et al . ; see Löwemark , for recent reviews), and recently by a high‐resolution digital image treatment (Dorador & Rodríguez‐Tovar ; Dorador et al . ,b; Rodríguez‐Tovar & Dorador , ).…”
Section: Ethological and Tracemaker Interpretationsmentioning
confidence: 99%
“…is generally assumed to be a trace of unknown deposit feeders (or partly chemichnia), among which sipunculids, polychaete annelids, arthropods or enteropneust hemichordates are the most commonly invoked tracemakers (Wetzel & Werner ; Kotake , ; Ekdale & Lewis ; Olivero & Gaillard , ; Löwemark & Grootes ; Löwemark et al . ; Löwemark ). Zoophycos is one of the most problematic burrow systems to study and interpret in the fossil record (Seilacher ).…”
Section: Introductionmentioning
confidence: 99%
“…They include deposit feeding (Wetzel and Werner, 1981;Ekdale and Lewis, 1991;Olivero and Gaillard, 1996), detritus feeding (Kotake, 1989(Kotake, , 1991(Kotake, , 1992, the refuse dump model (Bromley, 1991;Löwemark and Shäfer, 2003), the cache model (Fu and Werner, 1995;Bromley et al, 1999;Miller and D'Alberto, 2001;Bromley and Hanken, 2003;Löwemark and Shäfer, 2003;Löwemark, 2012) and the gardening model (Bromley, 1991;Löwemark et al, 2004;Gong et al, 2007Gong et al, , 2008. They include deposit feeding (Wetzel and Werner, 1981;Ekdale and Lewis, 1991;Olivero and Gaillard, 1996), detritus feeding (Kotake, 1989(Kotake, , 1991(Kotake, , 1992, the refuse dump model (Bromley, 1991;Löwemark and Shäfer, 2003), the cache model (Fu and Werner, 1995;Bromley et al, 1999;Miller and D'Alberto, 2001;Bromley and Hanken, 2003;Löwemark and Shäfer, 2003;Löwemark, 2012) and the gardening model (Bromley, 1991;Löwemark et al, 2004;Gong et al, 2007Gong et al, , 2008.…”
Section: Zoophycos Maker and Its Behaviour And Ethologymentioning
confidence: 99%